2021
DOI: 10.5814/j.issn.1674-764x.2021.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Enclosure on Plant and Soil Restoration in the Junggar Desert

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Furthermore, four diversity indices were calculated for each reservoir using TFL and eDNA detection data separately. Specifically, the Shannon-Wiener index [49], Pielou's evenness index [50], Chao1 index [51] and ACE index [52] were calculated following the previously established equations [53].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, four diversity indices were calculated for each reservoir using TFL and eDNA detection data separately. Specifically, the Shannon-Wiener index [49], Pielou's evenness index [50], Chao1 index [51] and ACE index [52] were calculated following the previously established equations [53].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have observed that grazing exclusion can significantly increase microbial diversity ( Wang et al., 2019 ; Zhang et al., 2019 ; Su et al., 2023 ), while others have found negligible or negative effects on soil microbial diversity ( Li et al., 2022 ; Fan et al., 2023 ; Guo et al., 2023 ). Furthermore, the direction and magnitude of response of microbial diversity to GE are largely determined by the duration of grazing exclusion and vary with microbial group, grassland type, soil depth, and climate conditions ( Aldezabal et al., 2015 ; Yao et al., 2018 ; Chen et al., 2020 ; Peng et al., 2021 ; Wu et al., 2022 ). Gaining insights into the patterns and controlling factors of grazing exclusion on soil microbial diversity is crucial for biodiversity preservation and resilience against grassland degradation.…”
Section: Introductionmentioning
confidence: 99%